แนวทางบริหารจัดการตลาดท่องเที่ยววัฒนธรรมสร้างสรรค์ของจังหวัดแพร่: Guideline for the Management of Creative Tourism in Cultural Tourist Market of Phrae - เกตุโศภิษฐ์, ปานณนาถ; เทพมา, อัมเรศ (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2024)
การศึกษาเรื่อง แนวทางบริหารจัดการตลาดท่องเที่ยววัฒนธรรมสร้างสรรค์ของจังหวัดแพร่ มีวัตถุประสงค์เพื่อ 1) ประเมินศักยภาพกิจกรรมการท่องเที่ยวบนพื้นฐานวัฒนธรรมสร้างสรรค์ของจังหวัดแพร่ และ2) แนวทางบริหารจัดการตลาดที่เหมาะสมต่อการพัฒนาของพื้นที่จังหวัดแพร่ การวิจัยแบบเชิงคุณภาพมีเครื่องมือในการศึกษา ประกอบด้วยแบบประเมินศักยภาพกิจกรรมท่องเที่ยวสร้างสรรค์ แบบสัมภาษณ์กึ่งมีโครงสร้าง และการอภิปรายกลุ่ม มีผู้ให้ข้อมูลมีคุณสมบัติ คือ มีประสบการณ์พัฒนาการท่องเที่ยวในพื้นที่จังหวัดแพร่มากกว่า 3 ปี เป็นการเลือกแบบเจาะจง ผลการศึกษาพบศักยภาพกิจกรรมท่องเที่ยวสร้างสรรค์ของจังหวัดแพร่ เป็นมรดกทางวัฒนธรรมทางด้านภูมิปัญญางานหัตถกรรมสร้างสรรค์ จำนวน 17 กิจกรรม และประเด็นการประเมินศักยภาพรายด้าน พบกิจกรรมมีเรื่องราวสร้างสรรค์มาจากพื้นฐานมรดกทางวัฒนธรรมมีคะแนนมากที่สุด และศักยภาพด้านการสื่อสารและการบอกเล่าเรื่องราวของผู้นำกิจกรรม พบว่ามีคะแนนน้อยที่สุด จากผลการประเมินศักยภาพและการอภิปรายกลุ่มทำให้ได้แนวทางบริหารจัดการตลาดท่องเที่ยววัฒนธรรมสร้างสรรค์ที่เหมาะสม ประกอบด้วย การจัดการด้านผลิตภัณฑ์ท่องเที่ยวสร้างสรรค์ การจัดการด้านราคา การจัดการด้านสถานที่จัดกิจกรรมสร้างสรรค์ การจัดการด้านส่งเสริมการตลาด และการจัดการด้านผู้ให้บริการท่องเที่ยวสร้างสรรค์ ทั้งนี้ พบกระบวนการจัดการเพื่อนำไปสู่ความสำเร็จของการท่องเที่ยววัฒนธรรมสร้างสรรค์ของพื้นที่จังหวัดแพร่ คือ การตั้งเป้าหมายพัฒนาพื้นที่ให้มุ่งสู่การท่องเที่ยววัฒนธรรมสร้างสรรค์ การประเมินทรัพยากรด้วยแนวคิด 3S (Story, Sense, Sophisticatio) การกำหนดแผนการทำงาน 5P (Participation, Product, Price, Place, Promotion) การติดตาม ประเมินผล เพื่อควบคุมให้เป็นไปตามแผนงานที่กำหนดไว้ให้มุ่งตอบเป้าหมายการพัฒนาพื้นที่ที่กำหนดไว้อย่างยั่งยืน The study of Guideline for the Management of Creative Tourism in the Cultural Tourist Market of Phrae province was intended to assess the potential of tourism activities based on the creative culture of Phrae province and to find a way for the manager of the market that was suitable for the development of Phrae province.This research is Qualitative research used educational tools consisting of potential tourism activities, semi-structured interviews, and group discussion. The informant was qualified, i.e. had experience of developing tourism in Phrae province for more than 3 years. It was a specific selection. The study found that assessing the potential of tourism activities based on the creative culture of Phrae province, was a cultural heritage in terms of wisdom, handicrafts and creativity, amounting to 17 activities. The potential assessment issues in each aspect found activities and creative stories based on cultural heritage as the most points. The ability to communicate and tell the story of the activity leader was found to have the lowest score. In this regard, from the results of the potential assessment and group discussions, guidelines for managing the creative cultural tourism market were appropriate, consisting of the management of creative tourism products, the price management, venue management for creative activities, the marketing promotion management, and management of creative travel service providers. In this regard, the management processes were founded to lead to the success of creative cultural tourism of Phrae province, which was to set a goal to develop the area towards creative cultural tourism by assessing resources with the 3S (Story, Sense, and Sophistication) concept. The determination of the 5P work plan (Participation, Product, Price, Place, Promotion) and the monitoring of evaluation in order to control it according to the specified work plan to meet the goals of sustainable development of the area.